2018
DOI: 10.1007/s40820-018-0230-4
|View full text |Cite
|
Sign up to set email alerts
|

Review of Water-Assisted Crystallization for TiO2 Nanotubes

Abstract: TiO2 nanotubes (TNTs) have drawn tremendous attention owing to their unique architectural and physical properties. Anodizing of titanium foil has proven to be the most efficient method to fabricate well-aligned TNTs, which, however, usually produces amorphous TNTs and needs further thermal annealing. Recently, a water-assisted crystallization strategy has been proposed and investigated by both science and engineering communities. This method is very efficient and energy saving, and it circumvents the drawbacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 162 publications
0
18
0
Order By: Relevance
“…In the literature, the crystallization of TiO 2 from the amorphous phase is described as a result of high-temperature annealing (Ref 26). As regards low-temperature alternatives, some other sources reported that it is possible to induce crystallization at room temperature with water or steam (Ref [22][23][24][25]. According to the knowledge of authors, crystallization of brookite as a result of moisture or condensed water has not been shown so far-all found reports describe crystallization of anatase.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, the crystallization of TiO 2 from the amorphous phase is described as a result of high-temperature annealing (Ref 26). As regards low-temperature alternatives, some other sources reported that it is possible to induce crystallization at room temperature with water or steam (Ref [22][23][24][25]. According to the knowledge of authors, crystallization of brookite as a result of moisture or condensed water has not been shown so far-all found reports describe crystallization of anatase.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, aligned NTs have been extensively reported in the literature for PEC water splitting applications. [42,[124][125][126] Table 1 provides some of the conventional techniques for the growth of NAs; however, in the case of TiO 2 NAs, electrochemical anodization techniques are used extensively. This fabrication method effectively controls NTs orientation and morphology.…”
Section: Titania (Tio 2 )-Based Aligned Nasmentioning
confidence: 99%
“…The controlled filling of nanotubes with drug-loaded polymeric micelles can generally slow down the release rate [163]. Drug reservoirs composed of TiO 2 nanorods, nanofibers, and nanotubes also exhibit a sustained drug release for dermal drug delivery applications [164][165][166].…”
Section: Therapeutic Deliverymentioning
confidence: 99%